AN ANALYTICAL INVESTIGATION OF VOLUNTARY REPORTING: A SECTORAL COMPARATIVE STUDY OF SERVICE AND MANUFACTURING COMPANIES LISTED ON THE DSE - Rakiv, Mohammad (Research In Management and Accounting (RIMA), 2025)
Voluntary disclosures are the disclosures that are presented in the annual reports of the companies voluntarily to increase the transparency, reliability and decision usefulness of the provided information. It boasts the confidence of the stakeholders as it proves the organization’s commitment towards the society, environment and ecosystem of the business. This paper aims to explore the level of disclosure provided by the listed companies of the Dhaka Stock Exchange (DSE) and to examine whether there are notable variances between the practices of voluntary disclosure by listed manufacturing and service companies. In total, 116 firms have been used as a sample for this particular investigation. This report is based on annual reports of the selected companies and content analysis technique has been applied. The findings of the study show that the average disclosure level of the sample companies is 68.58% with a standard deviation of 14.05%. The banking industry tops the list of reporting disclosures. Cement, NBFI, Food & Allied, IT, and Jute industry’s voluntary disclosure practices are greater than the average value and greater disparity in practices is observed in the Tannery, Food & Allied, and Insurance industry. When comparing the practice of the service company with that of the manufacturing companies, it can be inferred that the average disclosure level of the service companies is higher than the manufacturing companies with lower variation in practice. The result of the independent t-test shows that Levene’s test for equality of variances has a significance value of .001 which supports that there are significant differences in practice of voluntary reporting disclosure between service and manufacturing companies. The findings of the study will help policymakers to make better policies for the reporting of voluntary reporting in corporate annual reports.